WITTITE WITH SE-RICH COSALITE AND BISMUTHINITE FROM NEVSKOE TIN DEPOSIT (MAGADAN DISTRICT, RUSSIA) - Mozgova N.N.; Nenasheva S.N.; Efimov A.V.; Borodaev Yu.S.; Moëlo Y. (My University, 1992)
A second confirmed occurrence of wittite, one of the four known Pb-Bi-Se-sulfosalts, has been found in the Nevskoe tin deposit (Eastern Siberia). Microprobe analyses of wittite show pronounced variation of Se content (from 9.5 to 16.5 wt. %), due to S --> Se substitution; Pb and Bi contents vary from 29 and 43%, up to 34 and 46%, respectively. Minor elements are also present: Sb up to 1.5%, Ag up to 1.3 %, and Cu (0 to 0.2%). Comparison of microprobe data of wittite from Nevskoe and Falun, on the one hand, and cannizzarite from different deposits on the other hand, indicate that Ag is incorporated in the wittite/cannizzarite structure through the substitution 2 Pb -> Bi + Ag. Conversely, Ag substraction gives a constant Bi/(Bi + Pb) atomic ratio, independent of the Se/(Se+"S) ratio, and close to 55.1%. Se-rich wittite is compositionally very close to proudite and weibullite. X-ray powder and electron microdiffraction patterns are given; the incommensurate structure agrees with the 7H/12Q match along , like in wittite from Falun. Nevskoe wittite is close to Pb8Bi10(S, Se)23, but the 7H/12Q match requires the formula Pb11.61Bi14.26S33, with about 3% of the Pb atoms in the Q layer replaced by Bi atoms and vacancies (p). Taking into account all microprobe data, the general formula developed is: Pb11.61–2x0.13Agx(Bi14.26+x-ySby)(S1–zSez)33 with x and y 0.86 at., and z 0.45. At Nevskoe, associated bismuthinite contains from 5 to 12% Se, with minor Sb, Pb and Cu. Se-rich cosalite contains from 4 to 8% Se, with Sb from 2.7 to 5.3%, and minor Ag and Cu. Wittite in contact with cosalite clearly shows a relative Se-enrichment, that could be due to the pseudo-hexagonal sub-lattice of this incommensurate structure, very similar to the Bi2(Se, Te, S)3 sheet in the tetradymite series. According to microprobe data, there is a continuous change from Se-free cannizzarite to Se-rich wittite. Therefore, the validity of wittite as a specific mineral species appears questionable, and more accurate crystallographic studies on this incommensurate series are necessary.